Certain Subclasses of β-Uniformly q-Starlike and β-Uniformly q-Convex Functions. (16th September 2020) - AbuJarad, Eman S. A.; AbuJarad, Mohammed H. A.; Abdeljawad, Thabet; Jarad, Fahd
Abstract : In this paper, the authors introduced certain subclasses β -uniformly q -starlike and β -uniformly q -convex functions of order α involving the q -derivative operator defined in the open unit disc. Coefficient bounds were also investigated.